Micro and nanoplastics in human carcinogenesis: Insights from in vitro studies - Silva, Geovanna Carla Amaro [UNESP]; Fioretto, Matheus Naia [UNESP]; Lima, Micheli Canuto [UNESP]; Scarano, Wellerson Rodrigo [UNESP]; Delella, Flávia Karina [UNESP] (Elsevier, 2025)
Many types of cancer affecting humans have been investigated for centuries, underscoring their significance as a major global health challenge shaped by genetic, epigenetic, and environmental factors. In contrast, plastic production has only recently gained attention in healthcare, largely due to its degradation and the resulting formation of micronanoplastics (MNPs), which pose potential risks to both the environment and human health. In both contexts, experimental models are crucial for elucidating the mechanisms linking MNPs exposure to cancer, with in vitro studies serving as a key investigative approach. This narrative review compiles in vitro evidence on the effects of MNPs exposure across various tumor cell types. Current findings indicate that MNPs can bioaccumulate and disrupt organ-specific homeostasis, primarily through oxidative stress induction and interference with lipid peroxidation. Within tumor environments, the dose and physicochemical properties of MNPs play a decisive role in determining the severity of their effects. Overall, MNPs appear to activate signaling pathways that promote cell proliferation and tumor-specific invasiveness, thereby contributing to a tumor-promoting microenvironment. Based on available in vitro data, a possible correlation emerges between MNPs-induced carcinogenesis and the identification of potential biomarkers of plastic exposure and tumor progression. This review thus provides a critical foundation for future in vivo and clinical studies aimed at clarifying the role of MNPs in cancer development.